STUDI DEPLESI KULIT KAMBING PADA DELIMING MENGGUNAKAN (NH4)2SO4 - Prasetyo Hermawan; Alfani Risman Nugroho (Politeknik ATK Yogyakarta, 2018)
The purpose of this research is to study depletion on goat skin in the deliming process. The experiment was conducted using (NH4)2SO4 (ammonium sulfate) as deliming agent and using a jar test tool. Tests performed on pelt and liquid characters during the deliming process; pelt weight, pelt thickness, pH and contain nitrogen and sulfide of deliming liquid. Variations made of use (NH4)2SO4 is; 0, ½, 1.0, 1½, 2 and 2½ gr for 50gr of pelt. The results showed that the use of 1 gr (NH4)2SO4 decreases the pH of the liquid deliming pelt Ca(OH)2 from 11.0 to 8.9. Changes in the weight and thickness of pelt Ca(OH)2 in the use of 1gr (NH4)2SO4 are; 11% and 53% respectively. The use of 1gr (NH4)2SO4 and will produce the fastest rate in weight and thickness of pelt Ca(OH)2, namely each; 0.008% weight / minute and 0.02% thick / minute. In addition to 1gr (NH4)2SO4, the deliming liquid of pelt Ca (OH)2 has a final pH of 8.9 and from pelt NaOH has a final pH of 9.12. Pelt Ca(OH)2 on the use of 1gr (NH4)2SO4 has 13% compression and pelt NaOH on the use of 1.5gr (NH4) 2SO4 has compression 8.8%. The greater use of (NH4)2SO4 will produce fluid deliming with character greater nitrogen and sufide levels, except the lower sulfide levels for pelt Ca (OH)2 sulfide.